UTILIZATION OF RICE WASHING WATER AND EGG HELLS AS LIQUID ORGANIC FERTILIZER FOR GROWTH GREEN SAWI (Brassica juncea) - Nadia J. Rombe; Sandra E. Pakasi (Jurnal Agroekoteknologi Terapan, 2020)
Mustard greens (Brassica juncea) are a type of vegetable that is popular with people because of their delicious taste, easy access, easy cultivation, and high economic value after cabbage and broccoli. The Central Bureau of Statistics (2015) saw that the production of mustard plants from 2010 to 2013 has decreased. The production of mustard greens in 2010, 2011, 2012, and 2013 respectively was 240.78 tonnes; 196.57 tons; 169.20 tons; and 116.30 tons. Liquid organic fertilizer is a fertilizer that is available in liquid form, POC can be defined as a fertilizer that is made naturally through a fermentation process to produce a solution of decay from plant residues, as well as animal or human waste To increase the content of main nutrients such as nitrogen, phosphorus, and potassium, you can use rice washing water waste as water to water plants that can fertilize plants which can improve the quality of liquid fertilizers, especially the nutrient content of N, P and K. Based on the results of the analysis of eggshell content In the Soil Laboratory, it is known that eggshells contain 0.121% potassium, 8.977% calcium, 0.394% phosphorus, and 10.541% magnesium.Keywords: Mustard greens, Liquid organic fertilizer, Rice water, EggshellsAbstrakTanaman sawi hijau (Brassica juncea) merupakan jenis sayuran yang banyak digemari oleh masyarakat karena rasanya yang enak, mudah diperoleh, mudah untuk dibudidayakan serta memiliki nilai ekonomis yang tinggi setelah kubis dan brokoli. Badan Pusat Statistik (2015) produksi tanaman sawi dari tahun 2010 hingga 2013 mengalami penurunan. Produksi tanaman sawi pada tahun 2010, 2011, 2012 dan 2013 berurut-urut adalah 240,78 ton; 196,57 ton; 169,20 ton; dan 116,30 ton. Pupuk organik cair adalah pupuk yang tersedia dalam bentuk cair, POC dapat diartikan sebagai pupuk yang dibuat secara alami melalui proses fermentasi sehingga menghasilkan larutan hasil pembusukan dari sisa tanaman, maupun kotoran hewan atau manusia. Untuk meningkatkan kandungan unsur hara utama seperti nitrogen, fosfor, dan kalium dapat menggunakan limbah air cucian beras sebagai air untuk menyiram tanaman yang mampu menyuburkan tanaman yang dapat meningkatkan kualitas pupuk cair terutama kandungan unsur hara N,P dan K. Berdasarkan hasil analisis kandungan kulit telur di Laboratorium Tanah diketahui bahwa kulit telur mengandung unsur hara kalium sebesar 0,121%, kalsium sebesar 8,977%, fosfor sebesar 0,394% dan magnesium 10,541%.Kata Kunci : Tanaman Sawi hijau, Pupuk organik cair, Air beras, Cangkang telurÂ